2011
DOI: 10.1177/009318531103900103
|View full text |Cite
|
Sign up to set email alerts
|

Suggestibility and Fetal Alcohol Spectrum Disorders: I'll Tell You Anything You Want to Hear

Abstract: This article reviews the role of suggestibility as a psychological vulnerability in people with FASD who are arrested and questioned by police. After a review of relevant literature on suggestibility and FASD, preliminary data are presented from a small pilot study on suggestibility involving defendants with FASD in the United States who were involved in either a pre-trial or post-conviction adjudication process. Results of that study suggest that persons with FASD may be highly suggestible in interrogative si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 89 publications
(127 reference statements)
1
31
0
2
Order By: Relevance
“…, 2012). This population may also be more prone to acquiescence and may also change their responses even with just minimal pressure (e.g., Brown et al, 2010Brown et al, , 2011. There is also the tendency for this group to exhibit average but superficial verbal skills that mask their below-average comprehension ability (Fast & Conry, 2009).…”
Section: Risk Of False Confession False Testimony and Wrongful Convimentioning
confidence: 99%
See 1 more Smart Citation
“…, 2012). This population may also be more prone to acquiescence and may also change their responses even with just minimal pressure (e.g., Brown et al, 2010Brown et al, , 2011. There is also the tendency for this group to exhibit average but superficial verbal skills that mask their below-average comprehension ability (Fast & Conry, 2009).…”
Section: Risk Of False Confession False Testimony and Wrongful Convimentioning
confidence: 99%
“…Increasingly these terms are being replaced by the FASD with and without dysmorphic features in the (UK) (Sign, 2018). Individuals with FASD exhibit a variety of symptoms including cognitive (e.g., intelligence, executive control, and memory), social (e.g., communication skills and suggestibility), and adaptive (e.g., decision making ability and capacity to solve problems) impairments (Brown, Gudjonsson, & Connor, 2011;BoS, 2016). One of the misconceptions regarding FASD is that individual will exhibit facial features that would suggest PAE.…”
mentioning
confidence: 99%
“…Third, a clinical professional should be mindful of the impact of FASD symptoms on assessment strategies [22]. One consideration, is memory-related impairments (i.e., memory loss, suggestibility, and confabulation) and the association with reported misinformation that muddles the evaluation process [23,24]. Finally, the assessment of FASD often necessitates nuanced differential diagnosis, which may be beyond the skill sets of some professionals and thus requires consultation with an FASD expert.…”
Section: Implications For Mental Health Professionalsmentioning
confidence: 99%
“…Only two studies were identified which investigated the psycho-legal abilities of offenders with FASDs [8,39]. In a group of young offenders with FASDs, McLachlan, et al [8] investigated the psycho-legal abilities relevant to interrogation and adjudication in addition to assessing the offender's insight and confidence regarding their psycho-legal abilities.…”
Section: Evaluating the Psycho-legal Abilities Of Young Offenders Witmentioning
confidence: 99%
“…Another study involved a small pilot study conducted in the United States which investigated the role of suggestibility as a psychological vulnerability in defendants with FASD who were involved in a pre-trial or post-conviction adjudication process. Brown, et al [39] pilot study consisted of seven adults who were referred for multidisciplinary assessment by experts on FASD by counsel. All seven participants were male and ages ranged from 17 to 53 years of age, average age 29 years (African American, n = 4 and Caucasian, n = 3).…”
Section: Evaluating the Psycho-legal Abilities Of Young Offenders Witmentioning
confidence: 99%